The Chinese herbal formula Fuzheng Quxie Decoction attenuates cognitive impairment and protects cerebrovascular function in SAMP8 mice - Wang F (Dove Medical Press, 2018)
Feixue Wang,1 Jianchao Feng,2 Yang Yang,1 Jiangang Liu,3 Meixia Liu,1 Zhiyong Wang,1 Hui Pei,1 Yun Wei,1 Hao Li1 1Department of Geriatrics, Xiyuan Hospital of China Academy of Chinese Medical Sciences, Beijing, China; 2Intensive Care Unit, Heze Hospital of Traditional Chinese Medicine, Heze, Shandong, China; 3Department of Cardiology, Xiyuan Hospital of China Academy of Chinese Medical Sciences, Beijing, China Purpose: This study was designed to explore the underlying mechanism of action for a Fuzheng Quxie Decoction (FQD) in Alzheimer’s disease (AD), to validate its neuroprotective effects, and to provide experimental support for its predicted mechanism of action.Methods: An integrative approach to network pharmacology was performed to predict the mechanism of action for treatment of AD with FQD. The predicted mechanism was validated in SAMP8 mice.Results: With predicted putative FQD targets and a collection of AD-related genes, 245 possible regulatory targets of FQD were identified for the treatment of AD. Pathway-enrichment analysis for the possible regulatory targets indicated that vascular endothelial growth factor (VEGF) and VEGF-receptor signaling were pivotal in the treatment of AD with FQD. In vivo experiments confirmed the neuroprotective effect and the predicted mechanism of action for treatment of AD with FQD.Conclusion: This study contributes to an understanding of the neuroprotective effect of FQD and its potential mechanism of action for the treatment of AD. Keywords: Alzheimer’s disease, Fuzheng Quxie Decoction, network pharmacology, microcerebrovascular, vascular endothelial growth factor, hypoxia-induced factor 1α